3D‐QSAR, molecular docking, and ONIOM studies on the structure–activity relationships and action mechanism of nitrogen‐containing bisphosphonates - Liu, Qing‐Zhu; Wang, Shan‐Shan; Li, Xi; Zhao, Xue‐Yu; Li, Ke; Lv, Gao‐Chao; Qiu, Ling; Lin, Jian‐Guo (Chemical biology & drug design, 2018)
Nitrogen‐containing bisphosphonates (N‐BPs) have been used widely to treat various bone diseases by inhibiting the key enzyme farnesyl pyrophosphate synthase (FPPS) in the mevalonate pathway. Understanding the structure–activity relationships and the action mechanisms of these bisphosphonates is instructive for the design and the development of novel potent inhibitors. Here, a series of N‐BPs inhibitors of human FPPS (hFPPS) were investigated using a combination of three‐dimensional quantitative structure–activity relationship (3D‐QSAR), molecular docking, and three‐layer ONIOM studies. The constructed 3D‐QSAR model yielded a good correlation between the predicted and experimental activities. Based on the analysis of comparative molecular field analysis (CoMFA) contour maps, a series of novel N‐BPs inhibitors were designed and ten novel potent N‐BPs inhibitor candidates were screened out. Molecular docking and ONIOM (B3LYP/6‐31 + G*:PM6:Amber) calculations revealed that the inhibitors bound to the active site of hFPPS via hydrogen‐bonding interactions, hydrophobic interactions, and cation‐π interactions. Six novel N‐BPs inhibitors with better biological activities and higher lipophilicity were further screened out from ten candidates based on the calculated interaction energy. This study will facilitate the discovery of novel N‐BPs inhibitors with higher activity and selectivity. A 3D‐QSAR model was constructed for 53 N‐BPs with the inhibition activities on hFPPS. A series of novel N‐BPs inhibitors were designed and six novel N‐BPs inhibitors with better biological activities and higher lipophilicity were screened out. Molecular docking and ONIOM (B3LYP/6‐31 + G*:PM6:Amber) calculations showed that the inhibitors bound to the active site of hFPPS via hydrogen‐bonding interactions, hydrophobic interactions, and cation‐π interactions.